Trauma craniano violento: conhecimento parental e avaliação de material informativo - Lopes, Nahara Rodrigues Laterza (Universidade Federal de São Carlos, 2013)
This dissertation is a compendium of four scientific papers. Each paper describes a stage of the study, with the final goal of evaluating the effectiveness of different materials to increase parents knowledge on abusive head trauma. The first paper describes a review of national and international literature, which aimed to give a current overview of abusive head trauma (AHT). According to the review, AHT can be defined as injury to the skull and intracranial contents to a child due to a sudden unintentional impact and/or a violent shaking. It occurs mainly with babies and children under 1 year of age and can result in serious consequences for children's development, including death. Although there are specific signs for this type of abuse, it can be mistaken for common child illnesses or accidental head trauma. Thus, it is essential that health professionals are trained for the correct diagnosis. One of the main factors associated with its occurrence is the baby crying, which highlights the need for intervention with parents in order to teach them about child development and safe strategies to deal with the baby. The second paper aimed to investigate the knowledge of newborn parents about some characteristics associated with AHT, such as the pattern of the infant crying in the first months of life, strategies to deal with the crying baby and the consequences of shaking a baby. The results indicated a lack of knowledge about the severity of shaking a baby, as well as a possible Brazilian belief that babies should not be left crying alone. In this sense, there is a need for these issues to be addressed in AHT prevention efforts. The third paper aimed to investigate the belief of Brazilian parents about corporal punishment to infants, and its possible relation with abusive head trauma. As opposed to the international literature, participants of this study did not consider shaking as an appropriate strategy to discipline the baby, agreeing more with this strategy when it aimed to sooth the baby. Furthermore, the results indicated that the caregivers evaluation about the strategy s harm potential seems to influence its adoption in discipline and soothing contexts. Finally, the last paper describes the evaluation of the effectiveness of three different informational materials to increase knowledge of Brazilian parents about this type of abuse. The materials consisted of a video on abusive head trauma, a pamphlet individually read on the AHT, and a video on child safety, unrelated to AHT and used for comparison purposes. The results suggest that reading the pamphlet could be a useful strategy in prevention programs, since it increased participants' knowledge about the severity of shaking a baby, as well as the likelihood of using strategies to distance themselves from the baby when stressed by the crying. Although less significant, the results of the group who watched the video on the AHT also indicated an increase in knowledge about the average number of daily hours of baby crying. It is hoped that the results found in this dissertation will guide future AHT preventive efforts in Brazil.
Keywords: Psicologia do desenvolvimento; Violência intrafamiliar; Crianças maus-tratos; Trauma craniano violento; Síndrome do bebê sacudido; Violência física; Pediatric abusive head trauma; Shaken baby syndrome; Child maltreatment; Physical abuse; CIENCIAS HUMANAS::PSICOLOGIA